Perspectivism and identity: Literature, interpretation and appropriation of personal identity [Perspectivismo e identidad: Literatura, interpretación y apropiación de la identidad personal] (2018)
The two questions this paper deals with an approach to Nietzsche's texts. The first one is:how can be read the Nietzsche's sentence that there are no facts, only interpretations? And the second one is: what can be proposed instead of the subject to think personal identity? This approach is divided in four parts, each one answering a question and taking into account the conflict of interpretation and the ubiquity of language; the consequences of perspectivism for personal identity; the construction of identity as a half-way process between discovering and creating; and the aesthetical proposal of personal identity as an ethic option different to traditional morals. © 2018 Universidad de Murcia Servicio de Publicaciones. All rights reserved.